The relationship between curriculum innovation and graduates' quality level - Ari Eka Setyaningrum; Ifada Novikasari (Islamic perspective on Communication and Psychology, 2026)
Background: Curriculum innovation plays an important role in improving the competence, adaptability, and competitiveness of graduates in response to changing educational and societal demands. This study examines the relationship between curriculum innovation and graduate quality at SMA Muhammadiyah Boarding School Zam-Zam. Methods: This study employed a quantitative correlational approach. The population consisted of 236 alumni from the 2024/2025 academic year. An initial sample of 70 respondents was determined using the Slovin formula with a 10% margin of error and random sampling. Following data screening, 30 complete and valid responses were retained for statistical analysis. Data were collected using a five-point Likert-scale questionnaire and analyzed through validity, reliability, normality, linearity, Pearson correlation, and simple linear regression tests. Findings: The results demonstrate a strong and statistically significant positive relationship between curriculum innovation and graduate quality. Pearson correlation analysis produced an r value of 0.707 (p < 0.001), while simple linear regression showed a significant effect of curriculum innovation on graduate quality (F = 27.982, p < 0.001). The coefficient of determination (R² = 0.500) indicates that curriculum innovation explains 50% of the variance in graduate quality. The regression coefficient was positive (B = 0.854), indicating that higher levels of curriculum innovation are associated with higher graduate quality. Conclusion: Curriculum innovation has a significant and substantial relationship with graduate quality at SMA Muhammadiyah Boarding School Zam-Zam. Sustainable curriculum development, technological integration, Islamic boarding school values, and strengthening of 21st-century competencies are important components in supporting graduate quality. Novelty/Originality of this Article: This study provides empirical evidence on the relationship between curriculum innovation and graduate quality within an integrated Islamic boarding school context, contributing to the limited literature examining curriculum innovation and graduate outcomes in this educational setting.